The effect of oxytocin and Kisspeptin-10 in ovary and uterus of ischemia-reperfusion injured rats - M. Aslan; G. Erkanli Senturk; H. Akkaya; S. Sahin; B. Yılmaz (Elsevier, 2017)
Objective: Ischemia/reperfusion (I/R) injuries result in damage to endothelial and parenchymal cells. Oxytocin (OXY) stimulates uterine contraction during parturition and myoepithelial cells during suckling. OXY has been used as a protective antioxidant. Kisspeptin plays a key role in the central control of reproductive functions and onset of puberty. Recent studies show that these reproductive hormones have protective potential as antioxidant. The aim of this study is to investigate the potential protective effects of Kisspeptin and OXY as antioxidants on I/R injured ovary and uterus of female rats. Materials and methods: Rats were separated into five groups. Group 1, is control group; Group 2, rats were subjected to ischemia followed by reperfusion. Group 3, OXY administration 30 min prior to I/R applied rats; Group 4, Kisspeptin administration 30 min prior to I/R applied rats; Group 5, OXY and Kisspeptin administration 30 min prior to I/R. Ovary and uterus were removed for histopathological and biochemical observations. Malondialdehyde, glutathione levels, and superoxide dismutase activities were analyzed in order to observe antioxidant potential of OXY and Kisspeptin. Hematoxylin and Eosin staining was applied for histopathologic scoring. Results: Stromal and granulosa cells in ovary, endometrial cells in uterus were damaged in I/R group. The cellular damage of ovary and uterus were reduced in OXY and Kisspeptin administered I/R group when compared to only Kisspeptin injected I/R group and I/R group. There is no significant difference between OXY and OXY + Kisspeptin injected I/R groups. MDA levels were decreased in Kisspeptin and/or Oxytocin applied I/R group compared to I/R group. SOD activity and GSH levels were increased in Kisspeptin and/or OXY applied I/R group compared to I/R group. Conclusions: The present results suggest that exogenous application of oxytocin and kisspeptin can have antioxidant effects on the uterus and ovary.